The Role of the Transjugular Intrahepatic Porto-Systemic Shunt in an Emergency Setting - Alessandro Posa; Lorenzo Tenore; Pierluigi Barbieri; Giulia Mazza; Evis Sala; Roberto Iezzi (Life, 2023)
Transjugular intrahepatic porto-systemic shunt (TIPSS) is an interventional radiology procedure whose aim is to create artificial communication between the portal and the hepatic blood flow in order to reduce the pressure gradient in portal hypertension. The indications to perform a TIPSS procedure can be framed in an elective or emergency setting: refractory ascites to diuretic therapy and secondary prophylaxis of variceal hemorrhage are the most frequent reasons for executing a TIPSS in an election context, while acute uncontrolled variceal bleeding is the principal indication that a TIPSS needs to be performed in an emergency setting. In recent years, the role of the TIPSS has been redefined for several conditions, such as ectopic varices, portal vein thrombosis, Budd–Chiari syndrome, hepatic veno-occlusive disease, and many others. This review aims to perform a deep analysis of when and why a TIPSS procedure should be carried out in an emergency, pointing out the related most common technical difficulties and complications.